Human-centric lighting performance of shading panels in architecture: A benchmarking study with lab scale physical models under real skies. (1st July 2020) - Parsaee, Mojtaba; Demers, Claude M.H.; Lalonde, Jean-François; Potvin, André; Inanici, Mehlika; Hébert, Marc
Highlights: Shading panels (SPs) were analyzed in terms of human-centric lighting factors. Impacts of SPs' color, reflectance, orientation, and openness have been explored. Blue-color SPs increase melanopic units and generate colder daylighting. Red-color SPs decrease photopic units and produce warmer daylighting. Adaptive SPs must be developed to meet occupants' photobiological needs. Abstract: This study investigates shading panels' (SPs) impacts on daylighting features in a lab scale model in terms of parameters representing potential human eyes' biological responses identified as image forming (IF) and non-image forming (NIF). IF responses enable vision and NIF responses regulate internal body clocks known as circadian clocks. Human-centric lighting evaluates photopic units, representing IF responses, and melanopic units representing NIF responses, combined with correlated color temperature (CCT) of light for potential biological effects. SPs' impacts on such parameters of daylighting have not yet been studied. Previous research mostly studied panels' impacts on visual comfort and glare related to IF responses. This research explores the impact of SPs' color, reflectance, orientation, and openness on photopic and melanopic units and CCT of daylighting inside a 1:50 physical scale model of a space. Approximately 40 prototypes of SPs were evaluated. An experimental setup was designed under outdoor daylighting conditions to capture high dynamic range (HDR) images inside the model. HDR images were post processed to calculate and render the distribution of photopic and melanopic units, melanopic/photopic (M/P) ratios and CCTs in the captured viewpoint of the model. Results reveal the behavior of SPs' color, reflectance, orientation, and openness in modifying daylighting parameters related to biological responses. Bluish panels, in particular, increase daylighting melanopic units and CCTs whereas reddish panels increase photopic units and reduce CCTs. The research results were discussed to provide an outline for future developments of panels to adapt daylighting to occupants' IF and NIF responses.